2016
DOI: 10.3389/fnins.2016.00552
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for Region and Linguistic Specific nTMS-based DTI Fiber Tracking of Language Pathways in Brain Tumor Patients

Abstract: Navigated transcranial magnetic stimulation (nTMS) has recently been introduced as a non-invasive tool for functional mapping of cortical language areas prior to surgery. It correlates well with intraoperative neurophysiological monitoring (IONM) findings, allowing defining the best surgical strategy to preserve cortical language areas during surgery for language-eloquent tumors. Nevertheless, nTMS allows only for cortical mapping and postoperative language deficits are often caused by injury to subcortical la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 51 publications
1
60
2
Order By: Relevance
“…The technique of nTMS has lately been used to conduct language mappings in patients suffering from language-eloquent glioma or other entities of brain tumors [13][14][15][16]. Furthermore, it has been combined with diffusion tensor imaging (DTI) derived from preoperative magnetic resonance imaging (MRI) to provide spatially resolved maps that visualize language-related structures [17][18][19][20][21][22][23][24][25]. Integration into clinical routine and the perioperative workflow is seamless, and the approach is currently regarded as a valuable adjunct to intraoperative DES [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique of nTMS has lately been used to conduct language mappings in patients suffering from language-eloquent glioma or other entities of brain tumors [13][14][15][16]. Furthermore, it has been combined with diffusion tensor imaging (DTI) derived from preoperative magnetic resonance imaging (MRI) to provide spatially resolved maps that visualize language-related structures [17][18][19][20][21][22][23][24][25]. Integration into clinical routine and the perioperative workflow is seamless, and the approach is currently regarded as a valuable adjunct to intraoperative DES [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The mere additional use of nTMS-based DTI fiber tracking (DTI FT) did not improve the identification of DES-positive language areas during awake surgery [24]. Nevertheless, the visualization of the subcortical language network becomes possible purely based on functional data by using nTMS-based DTI FT, which has shown high potential for surgical planning, resection guidance, and risk assessment in patients with language-eloquent lesions [17][18][19][20][21][22][23][24][25]. However, explorations of the differences between language-positive and language-negative nTMS mappings are still largely missing, which is one reason contributing to the lack of understanding of the comparatively low specificity of nTMS language mapping in relation to intraoperative DES.…”
Section: Introductionmentioning
confidence: 99%
“…Publications on language tractography have focused on consensus protocols in normalized space or on the functionality of the white matter tracts [ 7 , 11 , 15 , 25 , 34 , 38 ]. However, those publications have not provided standard approaches on how to obtain reliable clinical language tractography results, i.e., in pathological brains, guided by cerebral structures or without the need for normalization [ 4 , 36 , 43 ]. Studies proposing the use of noninvasive cortical mapping results to place ROIs, which are linked with language function, suffer from the limited validation of the applied technology [ 9 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can visualize and calculate the electric field with its dose and orientation, as well as optimize the coil positioning continuously. The resolution of En-TMS reaches 2 mm [11,16]. At present, only the En-TMS system could be used for tumor-patient diagnostics [11][12][13][19][20][21].…”
Section: Electric-field Navigation and Line Navigationmentioning
confidence: 99%
“…In recent years, nTMS has been widely used in motor mapping, and more evidence shows that it is beneficial for patients with brain tumor. Many studies observed better outcomes and higher survival rates in brain tumor patients who use nTMS before surgery, thus expanding the initial role of nTMS as a mere preoperative planning tool [15,16].…”
mentioning
confidence: 99%